A Comparative Study on Public- Private Partnership (PPP) for Creating Highly Skilled and Productive Business Graduate in Bangladesh - Yunus, Mohammad (Asian Business Review, 2013)
Public Private Partnership (PPP) is a recent phenomenon in Bangladesh to upgrade quality education and create potential managerial manpower for smooth and sustainable economic development of this county which although, highly overpopulated, but lack skilled and worthwhile & effective managerial manpower. The course curriculum of both public and private universities especially BBA and MBA programs should be well designed and well patterned to satisfy needs of the county. The faculty of Business Administration of a Private university i.e BGC Trust University Chittagong and Faculty of Business Administration (FBA) of a public university, i.e University of Chittagong (CU), are trying to upgrade and improve syllabuses of both BBA and MBA in line with local North South University (Private University market leader) and other universities of North America, South East Asia and India. The rules, regulation, enactments etc must be made logical and attractive to fit accountability of teachers and others concerned. Training and development Programs must be befitting to enhance skills of teachers & other related human resources.JEL Classification Code:  E31
Keywords: Public-Private Partnership; Private University; Public University; Programs